Sedentary time and physical activity patterns of stroke survivors during the inpatient rehabilitation week. Issue 2 (12th March 2021) - de Jong, Amy U.; Smith, Moira; Callisaya, Michele L.; Schmidt, Matthew; Simpson, Dawn B.
Abstract : Physical activity is recommended after stroke. However, the rehabilitation day is largely spent sedentary. Understanding patterns of physical activity across the rehabilitation week may help identify opportunities to improve participation. We aimed to examine: (1) differences between weekday and weekend sedentary time and physical activity, (2) the pattern of 24-h rehabilitation activity. Participants with stroke ( n = 29) wore an activity monitor continuously during the final 7-days of inpatient rehabilitation. Linear mixed models (adjusted for waking hours) were performed with activity (sedentary, steps per day, walking time) as the dependent variable, and day type (weekday or weekend) as the independent variable. Patterns of upright time during the 24-h period were determined by averaging daily activity in 60-min intervals and generating a heat map of activity levels as a function of time. Participant mean age was 69 (SD 13) years (52% male) and mean National Institutes of Health Stroke Scale score was 7.0 (SD, 5.5). There was no significant difference in sedentary time between weekdays and weekends. At the weekend, participants spent 8.4 min less time walking (95% CI, −12.1 to −4.6) taking 624 fewer steps/day (95% CI, −951 to −296) than during the week. Activity patterns showed greatest upright time in the morning during the week. Afternoon and evening activities were low on all days. Sedentary time did not change across the 7-day rehabilitation week, but less walking activity occurred on the weekend. There are opportunities for stroke survivors to increase physical activity during afternoons and evenings and on weekend mornings during rehabilitation.